Molecular simulation and microtextural characterization of quartz dissolution in sodium hydroxide - Ali, A.M. (Springer, 2020)
This study uses empirical experimental evidence and Material Studio simulations to explain the interaction of sodium hydroxide (NaOH) with quartz. Density functional theory (DFT) calculations were carried out using the Cambridge Serial Total Energy Package. In addition, quartz grains subjected to dissolution in NaOH were characterized using scanning electron microscopy. The so-called O-middle termination in the quartz tetrahedron structure, typified by a solitary exposed oxygen atom at the surface, is the most susceptible SiO2 terminations to NaOH attack, as it is associated with the lowest surface energy. The adsorption energy values are â 1.44Â kcal/mol and â 5.90Â kcal/mol for a single atom layer and five-layered atomic structure, respectively. The DFT calculation reveals intramolecular energy is the dominant adsorption energy, followed by a weak van der Waals energy. The NaOH adsorbed on quartz (001) surface constitutes a lower band gap of 0.138Â eV compared to cleaved quartz (001) surface (0.157Â eV). In addition, the energy range of NaOH adsorbed on quartz is wider (â 50 to 10Â eV), compared to (001) quartz (â 20 to 11Â eV). The dissolved quartz showed the precipitation of sorbed silicate phases due to incongruent reactions, which indicates new voids and etch pits can be created through the cleaving of the sodium silicates sorbed into the quartz surface. The adsorption energy for NaOH interactions with reservoir sandstone was significantly higher compared to the solitary crystal grains, which can be attributed to the isotropic deformation of a single crystal, and non-uniform deformations of adjacent grains in granular quartz of sandstone reservoir. It can be inferred that exposure to NaOH will affect the structure and reactivity of quartz. The quartz surface textural study indicates that dissolution of crystalline (granite) and clastic rocks (sandstone) is critical to the development of voids, which will improve permeability by providing channels and routes for the passage of hydrothermal and reservoir fluids. Â© 2020, The Author(s).